(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SUMMARY: 1. Introduction - 2. The necessary conditions of social negotiation - 3. Nordic Secularism - 4. Organic religious literacy - 5. Translation - 6. Conclusion. ABSTRACT: The refusal to shake hands with a female reporter by a Muslim politician from the Miljöpartiet resulted in a controversy in Sweden. Together with a number of court cases, it revealed a disparity between the established judicial line and the views of the general public. The Swedish controversy received a response from Denmark, where the ruling coalition introduced new citizenship legislation with an obligation to shake hands with the mayor during a naturalization ceremony. These controversies highlighted the rising tensions on multiple levels, between majority and minority, religious freedom and gender equality, law and public opinion. This paper takes a closer look at the role of law as a negotiator and employs the notions of Nordic secularism, organic religious literacy, and the ethos of hospitality towards the untranslatable, in order to answer two questions: where these tensions come from and what are the possible ways of overcoming them.